Distributed Generation Placement Based on Voltage Stability Using Genetic Algorithm - Gholami, Alireza (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
In this thesis, a genetic algorithm (GA) based optimization is used to improve the voltage stability of a power network using Distributed Generation (DG) Units. GA determines the best places of DG Units in the power network. Also, the number and sizes of DGs used are calculated by the proposed algorithm. First, we have solved the problem without using GA. In this step, just one DG with constant size is considered. The main reason of using GA to solve the problem is that finding the best places of DGs could be very complicated and time consuming, considering the number and size of DGs. To evaluate and compare the possible solutions, an index called Voltage Index (VI), is proposed which shows the voltage stability of the power network. A Forward/Backward load flow is used to determine the bus voltages, and consequently the VI of the network. The results show that by using DGs the voltage stability of the network is improved. In addition, GA, as an optimization algorithm, can find the best solution for the problem considering number, size and place of DGs after a specific number of iterations. The best solution for the problem and the results of the load flow for best state are shown as the results of the thesis. Keywords: Power Systems, Distributed Systems, Distributed Generation, Renewable Energy Systems

ÖZ: Bu tezde, elektrik enerji sistemlerinde Dağıtılmış Üretim (DÜ) birimleri kullanarak gerilim kararlılığı genetik eniyileştirme algoritması (GA) kullanmak suretiyle iyileştirilmiştir. Bu algoritma kullanılarak, DÜ birimlerinin sayısı, büyüklükleri ve sistemde hangi noktalara yerleştirilecekleri belirlenmiştir. Bu problem ilk olarak GA kullanılmadan çözülmüştür. Bu aşamada, büyüklüğü sabit olan yalnız bir DÜ ele alınmıştır. GA kullanmanın esas nedeni, GA kullanılmadan yapılmaya çalışılan çözümün, DÜ’lerin sayıları ve büyüklükleri dikkate alındığında, oldukça karmaşık ve zaman alıcı bir işlem olmasıdır. Mümkün olan çözümleri değerlendirmek ve karşılaştırabilmek amacıyla, şebekenin gerilim kararlılığının bir göstergesi olarak, Voltaj Endeksi denilen bir endeks önerilmiştir. Bara gerilimlerini, ve sonuç olarak Voltaj Endeksini, hesaplamak amacıyla İleri/Geri yük akışı yöntemi kullanılmıştır. Sonuçlar, DÜ’ler kullanıldığında şebekenin gerilim kararlılığı iyileşmektedir. Ayrıca GA problemin en iyi çözümünü belirli bir tekrar sayısından sonra vermektedir. Bu çözüm DÜ’lerin sayısını, büyüklüklerini ve şebekede yerleştirilecekleri baraları içermektedir. Bu çözüm ve karşılık gelen şebekedeki yük akışı tezde sonuç olarak verilmiş ve tartışılmıştır. Renewable Energy Systems Anahtar Kelimeler: Güç Şebekeleri, Dağıtım Şebekeleri, Dağıtılmış Üretim, Yenilenebilir Enerji Şebekeleri.
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2017. Supervisor: Prof. Dr. Osman Kükrer.
Keywords: Electrical and Electronic Engineering; Electric power systems; Electric power system stability; Power Systems; Distributed Systems; Distributed Generation; Renewable Energy Systems